THEORETICAL SOURCES OF TEXT PRAGMALINGUISTIC ANALYSIS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
this article deals with the theories of text and pragmalinguistic analysis. In addition, author provides notions concerning pragmalinguistic and tex analysis as well as compares western scholar’s views and domestic linguists who contributed in the sphere of comparative linguistics.